Characterizing Dynamic Decay of Motion of Free-Standing Rocking Members. Issue 2 (May 2018) - Kalliontzis, Dimitrios; Sritharan, Sri
Rocking is likely the primary dynamic mode of vibration during the earthquake response of free-standing structural members. Previous research has routinely described the dynamic behavior of these members using a coefficient of restitution ( r ) modeling approach, which is shown in this paper to be insufficient for accurately capturing their decaying motion characteristics. Utilizing experimental testing and analytical investigation of concrete members, this study concludes that free-standing members dissipate energy in both a continuous manner and instantaneously at impacts at the rocking interface. Accounting for these two energy dissipation components is necessary to accurately produce rocking dynamic responses of free-standing blocks.